Allocation of entrepreneurial and innovative talent: An economic model based on institutionally-driven relative rewards - Vaillant , Yancy (2022)
To master the force of innovation that sparks economic prosperity and growth along the lines of Schumpeterian creative destruction, it is important to understand what guides the entrepreneurial and innovative talent needed to fuel this spark. This paper presents an economic model that mathematically develops and visually represents the entrepreneurial career decisions of individuals and the allocation of entrepreneurial talent across an economy. The model is based on an institutional theoretical framework, where the external formal or informal constraints (institutions) of local society guide the choices of individuals towards innovative entrepreneurial careers. This model closely derives from prior relative reward models developed by Acemoglu (1995) to explain how the local relative rewards structure governs the entrepreneurial career decisions of individuals, and these decisions determine the allocation of entrepreneurial and innovative talent in an economy.